Lifetime over 10000 hours for organic solar cells with Ir/IrOx electron-transporting layer - Li, Yanxun; Huang, Bo; Zhang, Xuning; Ding, Jianwei; Zhang, Yingyu; Xiao, Linge; Wang, Boxin; Cheng, Qian; Huang, Gaosheng; Zhang, Hong; Yang, Yingguo; Qi, Xiaoying; et al. (Nature communications, 2023)
The stability of organic solar cells is a key issue to promote practical applications. Herein, we demonstrate that the device performance of organic solar cells is enhanced by an Ir/IrO x electron-transporting layer, benefiting from its suitable work function and heterogeneous distribution of surface energy in nanoscale. Notably, the champion Ir/IrO x -based devices exhibit superior stabilities under shelf storing ( T 80 = 56696 h), thermal aging ( T 70 = 13920 h), and maximum power point tracking ( T 80 = 1058 h), compared to the ZnO-based devices. It can be attributed to the stable morphology of photoactive layer resulting from the optimized molecular distribution of the donor and acceptor and the absence of photocatalysis in the Ir/IrO x -based devices, which helps to maintain the improved charge extraction and inhibited charge recombination in the aged devices. This work provides a reliable and efficient electron-transporting material toward stable organic solar cells. Long-term stability of organic solar cells is critical to promote practical applications. Here, the authors utilize iridium/iridium oxide nanoparticles as the electron-transporting material and realize enhanced device stabilities under thermal aging with T70 of over 10000 h.